Effect of partial medial meniscectomy on the proprioceptive function of the knee - (:unkn) unknown (SPRINGER, 2010)
The aim of this study was to assess the proprioception of the partial meniscectomized knee and to assess if there is an effect on the knee proprioception. We performed a case-control study involving patients with meniscus tear at the posterior horn of medial meniscus. Group 1 composed of 19 patients, with an average age of 26.3 years, who were enrolled after sustaining an injury to the medial meniscus. Twenty healthy individuals, with an average age of 25.1, without history of knee injury, constituted Group 2. In order to document the proprioceptive capabilities of the knee, angle reproduction tests were performed. At a mean of 2 years after the surgery, there was no difference between the meniscectomized and healthy knee regarding the angle deviations in the lower flexion angles (15A degrees, 30A degrees, 45A degrees). However, mean knee joint position sense (KJPS) at 60A degrees reproduction in Group 1 and 2 was 64.3 (SD 5.3) and 69.2 (SD 4.9), respectively. Concomitantly, mean KJPS at 75A degrees reproduction in Group 1 and 2 were 80.1 (SD 6.59) and 74.4 (SD 5.6), respectively. Paired t test showed a statistically significant difference between Group 1 and 2 when compared to control angle deviations at 60A degrees and 75A degrees reproductions (P < 0.05). KJPS of the patients in meniscectomized group was poorer than the patients in healthy knee group at 60A degrees and 75A degrees knee flexion degrees. Those results indicated that even a partial absence of menisci causes a deterioration of proprioceptive functions of the knee.
Keywords: Knee; Meniscectomy; Proprioception; ANTERIOR CRUCIATE LIGAMENT; MENISCUS; RECONSTRUCTION; INNERVATION; ANATOMY; HUMANS